The Influence of Learning Models and Media on Students' Activities and Learning Outcomes on Acid Base Materials in High School - Angel, S. Ivy Florensyana; Silitonga, Pasar Maulim (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
Abstract: The Influence Of Learning Models And Media On Students' Activities And Learning Outcomes On Acid Base Materials In High School. This research aims to determine the influence of learning models, media, and the interaction between learning models and media on student learning activities and outcomes. The population in this study were all students of class XI MIPA at SMA Negeri 17 Medan, namely 6 classes. The sample for this research was taken randomly from 4 classes and the student sample was taken purposively, 10 people per class based on the homogeneity of their status. This research uses a 2 x 2 factorial design. Two factors are tested, namely factor A: Learning Model which consists of two levels, namely A1 = Discovery learning A2 = Guided inquiry, and factor B: learning media which consists of two levels, namely B1 = Video, B2 = PowerPoint. Learning acid-base material in high school which combines the guided inquiry learning model and video media provides higher activity and learning outcomes compared to the activities and learning outcomes of students who are taught by combining the guided inquiry + PowerPoint model, the combination of discovery learning + PowerPoint or a combination Discovery Learning model with video.Keywords: Discovery Learning, Guided Inquiry, Video, PowerPoint, Learning Results and Activities, Acids and Bases DOI: 10.23960/jppk.v13i1.29998